Znaczenie rachunku ekonomicznego w efektywnym zarządzaniu organizacją: The importance of economic accounting in the effective management of an organization - Drozdowski, Grzegorz (Management and Administration Journal, 2021)
This article aims to analyze the use of economic accounting in the flexible management of an organization. Improving the efficiency of an organization requires flexible management. This problem requires a definition of the concept of economic accounting in the literature. Furthermore, the article shows the importance of the role of economic accounting in the rational allocation of resources of an organization in different conditions.